1999
DOI: 10.1080/09595239996329
|View full text |Cite
|
Sign up to set email alerts
|

Causes and correlates of adolescent drug abuse and implications for treatment

Abstract: On the basis of the literature, the following risk factors for drug abuse by adolescents were identified: biological predisposition to drug abuse; personality traits that reflect a lack of social bonding; a history of low quality and consistency of family management, family communication, family relationships and parental role‐modelling, a history of being abused or neglected; low socio‐economic status; emotional or psychiatric problems; significant stressors and/or inadequate coping skills and social supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
14

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 138 publications
8
74
0
14
Order By: Relevance
“…A history of victimization is also strongly tied to current psychiatric symptoms of various kinds among adolescents, including depression, anxiety, difficulty concentrating, violent behavior, suicidal ideation, eating disorders, and self-harming behaviors; this finding is consistent with the results of earlier studies (2,3,7,22,27). Nearly one third of the study population had taken prescription drugs for these or other psychiatric disorders.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A history of victimization is also strongly tied to current psychiatric symptoms of various kinds among adolescents, including depression, anxiety, difficulty concentrating, violent behavior, suicidal ideation, eating disorders, and self-harming behaviors; this finding is consistent with the results of earlier studies (2,3,7,22,27). Nearly one third of the study population had taken prescription drugs for these or other psychiatric disorders.…”
Section: Discussionsupporting
confidence: 89%
“…Because the causal connection is unclear, some researchers argue that victimization primarily results in various psychiatric symptoms (e.g., anxiety, depression, post-traumatic stress disorder, conduct disorder, risk taking of various kinds), which in turn may lead to both experimental drug use and later to addictive disorders of a more serious nature (3,7,22,27). The degree of victimization is often related to the degree of psychiatric disorder (2,28).…”
Section: Victimization In Relation To Drug and Alcohol Usementioning
confidence: 99%
See 2 more Smart Citations
“…Research on the aetiology of drug use (Hawkins et al 1995;Spooner 1999) has shown that it is one of a number of types of problem behaviour in adolescence (Jessor 1998) that includes crime (Jessor 1998;National Crime Prevention 1999;Loeber & Farrington 2000) and poor mental health and school dropout, all of which share common antecedents and impair preparation for adulthood. Shared risk factors for drug use and other problem behaviours include: individual characteristics (e.g.…”
Section: Aetiology Of Drug Use and Other Problem Behavioursmentioning
confidence: 99%